Total quality management and customer service efficiency in selected energy organizations in Nigeria - Adedoyin, Samuel Adeyemi; Asomwonriri, Wilfred Ahem; Akpobire, Ufoma Ohwoferia (Management and Entrepreneurship: Trends of Development, 2025)
The research examined the effect of total quality management on customer service efficiency in two selected energy organizations in Nigeria. The study sought to establish the effects of customer focus, continuous improvement, and process management as dimensions of total quality management on customer service efficiency in the sampled organizations. The population of the study were the employees of both organizations. A combination of purposive, stratified and convenience sampling approaches was employed in this study. The representativeness of the sample was assured by engaging stratified sampling wherein we ensured that the respondents were from across the various strata of both organizations in the three cities of interest. A properly structured questionnaire was used as the survey instrument and a total of 360 copies of the research instrument were distributed to the two organizations across the three cities. A response rate of about 75% was obtained as only 273 copies of the instrument were returned and found usable. The hypotheses were tested using regression analysis. The result confirms that there is a significant positive effect of customer focus, continuous improvement, and process management as dimensions of total quality management on customer service efficiency in both organizations. The study recommended that policies and practices that facilitate customer focus, continuous improvement, and process management should be encouraged to improve customer service efficiency in the organizations. JEL Classification: M10, M11, M30